EMPOWERING WOMEN THROUGH EDUCATION: UNVEILING THE PATH TO SOCIOECONOMIC PROGRESS IN PAKISTAN - Umar Daraz; Wasif Khan; Zakir Hussain; Aziz Ul Hakim; Ibrahim (International Journal of Contemporary Issues in Social Sciences, 2024)
Purpose- This study investigates education's impact on women's socioeconomic advancement in Pakistan's Malakand Division, considering its unique sociocultural dynamics. Addressing gender disparities in education and economic opportunities, the research aligns with national discussions on gender empowerment and education, offering localized insights. Methodology- Employing a mixed-methods approach, the study first samples educated women from all nine districts using stratified random sampling and validated questionnaires. Quantitative analysis indicates consensus on education's positive influence and establishes a significant correlation between education and socioeconomic progress. Qualitative insights are gathered through interviews and focus group discussions, revealing themes of challenging norms, empowerment, and economic participation. The explanatory sequential methodology combines quantitative and qualitative data for a comprehensive narrative. Findings- The study demonstrates that education yields diverse benefits for women in Malakand Division, encompassing economic growth, improved health, and altered life trajectories. Integrating quantitative and qualitative results highlights education's multifaceted impact. Practical Implications- Policy recommendations include gender-responsive education, maternal health awareness, women's employment support, gender-neutral family norms, financial literacy, and tailored educational initiatives. These steps are vital for enhancing women's empowerment and reducing gender disparities. Social Implications- By showcasing education's transformative role, this study challenges societal norms and contributes to the broader gender equality discourse in Pakistan. Originality Value- This research's originality lies in its focus on the specific sociocultural dynamics of Malakand Division. The combined mixed-methods approach provides unique insights into the link between education and women's socioeconomic advancement, informing localized strategies and policies.